Experimental Study for the Embedded Depth of Support Structure Foundation Pit in Granite Residual Soil Area - Yi-ao Liu; Chang-ming Wang; Rui-yuan Gao; Bai-long Li; Xiao-yang Liu; Zhu Liang; Nan Jiang; Zhi-dong Chen (Advances in Civil Engineering)
In order to deeply understand the appropriate embedded depth of the foundation pit diaphragm wall in granite residual soil area, a physical model of the diaphragm wall with inner support for foundation excavation was constructed according to the actual project in the proportion of 1 : 30. The distribution of Earth pressure, the horizontal displacement of the wall, and the settlement behind the wall were obtained by physical experiments. The numerical simulation was then performed to authenticate the results from physical modeling. It was observed that the embedded depth of the diaphragm wall had the most obvious influence on the horizontal displacement of the wall. Moreover, the final soil settlement and its influence were significantly increased with the decrease in embedded depth. The analysis results also suggested that the control value for the embedded depth of the wall should not be less than 0.36 H (H is the excavation depth of the foundation pit).